2020
DOI: 10.1503/cmaj.200375
|View full text |Cite
|
Sign up to set email alerts
|

Closing the gender pay gap in Canadian medicine

Abstract: Women in Canadian medicine consistently earn less than men. • The pay gap between women and men exists within every medical specialty and also between specialties, with physicians in maledominated specialties receiving higher payments. • The gender pay gap in medicine is not explained by women working fewer hours or less efficiently but, rather, relates to systemic bias in medical school, hiring, promotion, clinical care arrangements, the fee schedule itself and societal structures more broadly. • Actions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 68 publications
1
70
0
9
Order By: Relevance
“… 9 Grand rounds are opportunities to model leaders and diversity in medicine; however, a 2018 retrospective study of presenters at medical grand rounds at 5 major academic hospitals in Canada showed that women are underrepresented. 10 Women are more likely to work in lower paid and typically undervalued areas of medicine, 11 , 12 obtain reference letters for medical school faculty positions that are less supportive than their male counterparts, 13 and experience a decreased likelihood of being addressed by their professional title, 14 , 15 than men. In both academia and in practice, women are paid less than their male counterparts even after adjusting for several factors, such as age, experience and workload; 11 , 12 indeed, estimates suggest that women are paid an average of 30% to 40% less than men through fee-for-service models of payment for family doctors and specialists, respectively.…”
Section: What Is the Scale Of Gender Inequity In Medical Leadership In Canada?mentioning
confidence: 99%
See 1 more Smart Citation
“… 9 Grand rounds are opportunities to model leaders and diversity in medicine; however, a 2018 retrospective study of presenters at medical grand rounds at 5 major academic hospitals in Canada showed that women are underrepresented. 10 Women are more likely to work in lower paid and typically undervalued areas of medicine, 11 , 12 obtain reference letters for medical school faculty positions that are less supportive than their male counterparts, 13 and experience a decreased likelihood of being addressed by their professional title, 14 , 15 than men. In both academia and in practice, women are paid less than their male counterparts even after adjusting for several factors, such as age, experience and workload; 11 , 12 indeed, estimates suggest that women are paid an average of 30% to 40% less than men through fee-for-service models of payment for family doctors and specialists, respectively.…”
Section: What Is the Scale Of Gender Inequity In Medical Leadership In Canada?mentioning
confidence: 99%
“…Because implicit gender bias is common and, by definition, largely unrecognized, 42 , 43 gender bias training is necessary for people involved in candidate selection, although without clear measures to effect behaviour change such training may be insufficient. Open and transparent procedures and policies support more equitable hiring of academic and clinician candidates, 11 and open search procedures (including job postings) should embed equity requirements. For example, all eligible candidates must be encouraged to apply and active strategies to increase the diversity of applicants should be undertaken.…”
Section: How Can We Achieve Gender Equity In the Medical Profession?mentioning
confidence: 99%
“…This may be due to the gender pay gap that exists, where women are remunerated less than their male colleagues in urology 38 and other specialties in medicine. 39,40 In Canada, urology ranks the most disparate in gross payments to male vs. female physicians (ratio of 1.6). 39 These gender-based income disparities remain true even after adjustment for age, years in practice, patient factors, and surgical specialty.…”
Section: Burnout In Female Urologistsmentioning
confidence: 99%
“…39,40 In Canada, urology ranks the most disparate in gross payments to male vs. female physicians (ratio of 1.6). 39 These gender-based income disparities remain true even after adjustment for age, years in practice, patient factors, and surgical specialty. 41 This may be explained by the higher proportion of female specific procedures (i.e., slings) performed by female urologists, 42 and the poorer compensation for female-specific procedures when compared to male-specific procedures of similar complexity.…”
Section: Burnout In Female Urologistsmentioning
confidence: 99%
“…Neither individual characteristics nor workplace effects reduced the unexplained portion of the gender gap substantially (Drolet and Mumford 2012). In some fields in Canada, such as medicine, the gender pay gap was not explained by women's work habits but was related to systemic bias across the career (Cohen and Kiran 2020). This pattern was also found at the national level.…”
Section: Gender Income Gap Domestic Work Inequalities and Theoretical Frameworkmentioning
confidence: 89%